The Mongols - Morgan, David, 1945- (Malden, MA : Blackwell Publishing, 2007)
Provides an overview of the government, religion, and politics of the Mongolian Empire. Considers the effects of Mongol military campaigns on other countries and peoples in China, Russia, Persia, and Europe. Assesses the astonishing military career of Chingiz (Genghis) Khan. Includes an epilogue assessing the contribution of recent scholarship to our understanding of the Mongols history. Well-illustrated by maps and photographs throughout.
1. The study of Mongol history -- 2. Nomads of the steppe: Asia before Chingiz Khan -- 3. Chingiz Khan and the founding of the Mongol Empire -- 4. Nature and institutions of the Mongol Empire -- 5. The Mongols in China -- 6. Expansion to the west: the Mongols in Russia and Persia -- 7. The Mongols and Europe -- 8. What became of the Mongols? -- 9. The Mongol Empire since 1985.
BIBINDX
Keywords: Mongols -- History